Genetic and clinical phenotypic analysis of carney complex with external auditory canal myxoma - Wan, Wei; Zeng, Liang; Jiang, Hongqun; Xia, Yunyan; Xiong, Yuanping (Frontiers in Genetics, 2022)
Background: Mutations in PRKAR1A gene can lead to Carney complex (CNC), and most CNC patients develop cardiac and cutaneous myxomas. In particular, cardiac myxomas are a common cause of mortality in CNC patients. Cutaneous myxomas of the external ear are extremely rare, and do not have any specific clinical features Methods: In this retrospective study, we analyzed the clinical and genetic data of the proband and his family and fifty whole blood control samples selected from the molecular genetic database of our hospital . Whole exome DNA sequencing analysis was used to detect the mutation in the peripheral blood samples. Results: The results of the clinical analysis showed the presence of spotty skin pigmentation and external auditory canal myxoma in the proband as well as in his sister and mother. Whole-exome DNA sequencing showed a novel heterozygous mutation in the PRKAR1A gene i.e., c.824_825delAG (p.Gln275Leufs*2), in the proband and his sister and mother Conclusion: In conclusion, the family members had the same autosomal dominant PRKAR1A mutation. DNA sequencing revealed a novel c.824_825delAG in exon 9 of PRKAR1A. This pathogenic mutation has not been reported previously, and may be related to the occurrence of external auditory canal myxomas and spotty pigmentation. This study broadens the genotypic spectrum of PRKAR1A mutations in CNC.